Border odyssey : travels along the US/Mexico divide - Thompson, Charles D., Jr. (Charles Dillard), 1956- (University of Texas Press, 2015)
"Border Odyssey takes us on a drive toward understanding the U.S./Mexico divide: all 1,969 miles -- from Boca Chica to Tijuana -- pressing on with the useful fiction of a map ... Along the journey, five centuries of cultural history (Indigenous, French, Spanish, Mexican, African American, colonist, and U.S.), wars, and legislation unfold. And through observation, conversation, and meditation, Border Odyssey scopes the stories of the people and towns on both sides ..."--Jacket.